2011
DOI: 10.1111/j.1468-3083.2011.04299.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor‐I gene polymorphism in acne vulgaris

Abstract: Our results suggest that IGF-I (CA) 19 polymorphism may contribute to a predisposition to acne in Turkish patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 18 publications
(25 reference statements)
3
43
0
7
Order By: Relevance
“…9 A study by Tasli et al has suggested that insulin like growth factor-1 cytosine-adenine repeat (IGF-1 CA 19) polymorphism may contribute to a predisposition to acne in Turkish patients. 1 A study by Balta et al suggested that insulin resistance may not play a major role in the pathogenesis of post-adolescent acne.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 A study by Tasli et al has suggested that insulin like growth factor-1 cytosine-adenine repeat (IGF-1 CA 19) polymorphism may contribute to a predisposition to acne in Turkish patients. 1 A study by Balta et al suggested that insulin resistance may not play a major role in the pathogenesis of post-adolescent acne.…”
Section: Discussionmentioning
confidence: 99%
“…1 Even though acne is considered an androgen-dependent disease, occurrence of acne doesn't correlate with plasma androgen levels. Increased serum levels of insulin like growth factor (IGF-1) have been observed in adult women and men with acne, giving rise to the possibility of the role of growth hormone (GH), hyperinsulinemia, and IGF1 in acne.…”
Section: Introductionmentioning
confidence: 99%
“…The highest physiological IGF-1 serum levels are found between the 15 th and 20 th year of life, which parallels the age with the highest acne prevalence. An IGF-1 gene polymorphism associated with acne has been identifi ed [ 18 ] . Insulin-like growth factor 1 triggers keratinocyte proliferation.…”
Section: Pathogenesismentioning
confidence: 99%
“…14, 15 Saleh et al, num estudo caso controlo, avaliaram os níveis séricos de hormona de crescimento e IGF-1 em pacientes com acne severa e compararam com os níveis de indiví-duos saudáveis e com acne moderada e leve, mostrando um aumento significativo da hormona de crescimento e da IGF-1, e consequentemente de vários androgénios, nos doentes com acne severo. 14 Tasli et al mostraram também que os polimorfismos do IGF-1 podem contribuir para um aumento da Figura 1 -Mecanismos pelos quais a IGF-1 potencia a ação andró-gena.…”
Section: Métodosunclassified
“…15 Para além disso, este estudo de Tasli et al mostrou que os pacientes com sintomatologia severa apresentam polimorfismos estaticamente diferentes dos indivíduos saudáveis e com acne leve a moderado. 15 Apesar da IGF-1 e da hormona de crescimento promoverem a inflamação e a comedogénese, são os fatores de transcrição da célula da glândula sebácea, os responsáveis pela regulação fina desse estímulo, sendo estes influenciados por fatores da dieta do indivíduo. 16,17 ( Fig.…”
Section: Métodosunclassified